Severe reaction to radiotherapy provoked by hypomorphic germline mutations in ATM (ataxia–telangiectasia mutated gene). Issue 10 (3rd August 2020) - Asadollahi, Reza; Britschgi, Christian; Joset, Pascal; Oneda, Beatrice; Schindler, Detlev; Meier, Urs R.; Rauch, Anita
Abstract: Background: A minority of breast cancer (BC) patients suffer from severe reaction to adjuvant radiotherapy (RT). Although deficient DNA double‐strand break repair is considered the main basis for the reactions, pretreatment identification of high‐risk patients has been challenging. Methods: To retrospectively determine the etiology of severe local reaction to RT in a 39‐year‐old woman with BC, we performed next‐generation sequencing followed by further clinical and functional studies. Results: We found a −4 intronic variant (c.2251‐4A>G) in trans with a synonymous (c.3576G>A) variant affecting the ATM DNA‐repair gene (NG_009830.1, NM_000051.3) which is linked to autosomal recessive ataxia–telangiectasia (A–T). We verified abnormal transcripts resulting from both variants, next to a minor wild‐type transcript leading to a residual ATM kinase activity and genomic instability. Follow‐up examination of the patient revealed no classic sign of A–T but previously unnoticed head dystonia and mild dysarthria, a family history of BC and late‐onset ataxia segregating with the variants. Additionally, her serum level of alpha‐fetoprotein (AFP) was elevated similar to A–T patients. Conclusion: Considering the variable presentations of A–T and devastating impact of severe reactions to RT, we suggest a routine measurement of AFP in RT‐candidate BC patients followed by next‐generation sequencing with special attention to non‐canonical splice site and synonymous variants in ATM . Abstract : Severe local reaction to standard radiotherapy has devastating impact on breast cancer patients and reliable prediction has been difficult. We provide further evidence for hypomorphic biallelic variants in the DNA‐repair gene ATM as an important underlying cause for both, breast cancer and hypersensitivity to radiotherapy. We therefore discuss routine screening of serum alpha‐fetoprotein as a biomarker for ATM deficiency in radiotherapy‐candidate breast cancer patients followed by next‐generation sequencing with special attention to non‐canonical splice‐site and synonymous variants in the ATM gene.